Taxonomy of Indonesian giant clams (Cardiidae, Tridacninae) (Biodiversitas Journal of Biological Diversity, 2012)
Hernawan E. 2012. Taxonomy of Indonesian giant clams (Cardiidae, Tridacninae). Biodiversitas 13: 118-123. A taxonomic study was conducted on the giant clam’s specimens deposited in Museum Zoologicum Bogoriense (MZB), Cibinong Indonesia. Taxonomic overviews of the examined specimens are given with diagnostic characters, remarks, habitat and distribution. Discussion is focused on specific characters distinguishing each species. From seven species known to distribute in Indonesian waters, there are six species,Tridacna squamosa Lamarck, 1819; T. gigas Linnaeus, 1758; T. derasa Roding, 1798; T. crocea Lamarck, 1819; T. maximaRoding,1798; and Hippopus hippopus Linnaeus, 1758. This study suggests the need for collecting specimen of H. porcellanus Rosewater, 1982. Important characters to distinguish species among Tridacninae are interlocking teeth on byssal orifice, life habits, presence of scales and inhalant siphon tentacles.
Keywords: Tridacninae, taxonomy, Museum Zoologicum Bogoriense